Effects of Supraphysiological Doses of Steroids on the Left Ventricle of Sedentary Mice: Morphometric Analysis - de Souza, Érika Larissa Poscidônio; Dias, Rodrigo Leandro; Rios, Raíssa Santiago; Vieira, Tânia Martins; Damião, Bruno; Rossi, Wagner Costa, Junior; Esteves, Alessandra (Journal of Morphological Sciences, 2019)
Anabolic androgenic steroids (AAS) are synthetic compounds derived from testosterone, which are widely used in supraphysiological doses by people seeking an aesthetic effect. The objective of the present experiment was to evaluate the possible morphometric changes in the cardiac left ventricle caused by the administration of supraphysiological doses of the anabolic steroids testosterone cypionate and stanozolol in the hearts of young sedentary mice, to serve as a comparative parameter with young mice that were submitted to exercise. We have used 60 hearts of sedentary young Swiss mice, aged ∼ 90 days old (young-adult), with a body weight between 40 and 50 g. The animals were divided into three groups: the control group, the testosterone cypionate group, and the stanozolol group. For the analysis, 10 distinct sections of the apex, of the middle region, and of the base of the heart were selected, followed by an optical microscope measurement with a 2.5x magnification. The results obtained show an increase in both myocardial thickness and left ventricular cavity diameter in the two groups of male animals in relation to the control group; however, in females, an increase in the thickness of the left ventricular myocardium was observed only for the stanozolol group. These results suggest that the cardiac alterations observed in the present study may be directly related to some signs and symptoms already described in the literature, such as hypertension, arrhythmias, infarction, sudden death, and other cardiovascular diseases.
Keywords: heart; morphometric analysis; left ventricle; steroids